Telomerase-Mediated Strategy for Overcoming Non–Small Cell Lung Cancer Targeted Therapy and Chemotherapy Resistance - Ilgen Mender; Ryan LaRanger; Krishna Luitel; Michael Peyton; Luc Girard; Tsung-Po Lai; Kimberly Batten; Crystal Cornelius; Maithili P. Dalvi; Michael Ramirez; Wenting Du; Lani F. Wu; et al. (Neoplasia: An International Journal for Oncology Research, 2018)
Standard and targeted cancer therapies for late-stage cancer patients almost universally fail due to tumor heterogeneity/plasticity and intrinsic or acquired drug resistance. We used the telomerase substrate nucleoside precursor, 6-thio-2′-deoxyguanosine (6-thio-dG), to target telomerase-expressing non–small cell lung cancer cells resistant to EGFR-inhibitors and commonly used chemotherapy combinations. Colony formation assays, human xenografts as well as syngeneic and genetically engineered immune competent mouse models of lung cancer were used to test the effect of 6-thio-dG on targeted therapy– and chemotherapy-resistant lung cancer human cells and mouse models. We observed that erlotinib-, paclitaxel/carboplatin-, and gemcitabine/cisplatin-resistant cells were highly sensitive to 6-thio-dG in cell culture and in mouse models. 6-thio-dG, with a known mechanism of action, is a potential novel therapeutic approach to prolong disease control of therapy-resistant lung cancer patients with minimal toxicities.